Services innovation and economic performance: An analysis at the firm - Lopes, Luisa Ferreira (2008)
In this paper we estimate a model linking innovation effort and economic performance, along the lines of the Mairesse and Mohnen (2003) model. We examine this relationship in the context of services sectors instead of Research and Development intensive manufacturing sectors. Much effort has already been made to explore the innovation-performance relationship for manufacturing sectors but it is still much understudied for services, particularly for Portugal. In this paper we aim to take a step in fulfilling this gap. We use new firm level data for ten services sectors from the Second Community Innovation Survey of Portugal, to estimate the model.